A consensus-based transparency checklist - Aczel, Balazs (Nat Hum Behav, 2019)
We present a consensus-based checklist to improve and document the transparency of research reports in social and behavioural research. An accompanying online application allows users to complete the form and generate a report that they can submit with their manuscript or post to a public repository.